2014
DOI: 10.3390/rs61010002
|View full text |Cite
|
Sign up to set email alerts
|

Irrigated Grassland Monitoring Using a Time Series of TerraSAR-X and COSMO-SkyMed X-Band SAR Data

Abstract: Abstract:The objective of this study was to analyze the sensitivity of radar signals in the X-band in irrigated grassland conditions. The backscattered radar signals were analyzed according to soil moisture and vegetation parameters using linear regression models. A time series of radar (TerraSAR-X and COSMO-SkyMed) and optical (SPOT and LANDSAT) images was acquired at a high temporal frequency in 2013 over a small agricultural region in southeastern France. Ground measurements were conducted simultaneously wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
73
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 86 publications
(100 reference statements)
5
73
0
Order By: Relevance
“…The decrease in the radar signal sensitivity to the soil moisture when the vegetation cover increases was reported in the studies of Baghdadi et al [30] and El Hajj et al [44]. In Baghdadi et al [30], the sensitivity of the radar signal at the C-band (VV polarization and high incidence angle) is 0.11 dB/[vol %] and 0.05 dB/[vol %] for a grassland biomass lower and higher than 1 kg/m 2 , respectively.…”
Section: Sar Signal Sensitivity Analysismentioning
confidence: 90%
“…The decrease in the radar signal sensitivity to the soil moisture when the vegetation cover increases was reported in the studies of Baghdadi et al [30] and El Hajj et al [44]. In Baghdadi et al [30], the sensitivity of the radar signal at the C-band (VV polarization and high incidence angle) is 0.11 dB/[vol %] and 0.05 dB/[vol %] for a grassland biomass lower and higher than 1 kg/m 2 , respectively.…”
Section: Sar Signal Sensitivity Analysismentioning
confidence: 90%
“…Several studies showed that the correlation between the NDVI and the vegetation parameters (LAI, VWC, biomass, etc.) is strong when the NDVI is less than 0.7-0.8 [21][22][23]. Beyond 0.7-0.8, the NDVI saturates and does not vary with the increase of the vegetation parameters.…”
Section: Introductionmentioning
confidence: 88%
“…Beyond 0.7-0.8, the NDVI saturates and does not vary with the increase of the vegetation parameters. For example, the logarithmic relationship observed between NDVI and LAI saturates when the LAI exceeded 2-3 m 2 /m 2 [6,[21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…A similar outcome has been observed in studies focused on the use of SAR backscatter for agricultural monitoring. Hajj et al [43] reported that the X-band HV polarisation is more sensitive to grasslands parameters than HH. Additionally, Baghdadi et al [16] concluded that the co-pol channels (HH and VV) have a slightly lower potential for the detection of the sugarcane harvest.…”
Section: Groupmentioning
confidence: 99%